Deinstitutionalization second time around – What can we learn from the psychiatric experience? - Uri Manor; Gad Segal (Digital Health)
This historical opinion article draws parallels between mid-20th-century psychiatric deinstitutionalization and today's rapid expansion of home-based medical care. While psychiatric conditions differ fundamentally from acute medical illnesses, lessons from deinstitutionalization can inform current and future telemedicine models. Deinstitutionalization resulted from social, legal, and pharmaceutical advances but also produced unforeseen consequences, including increased incarceration, homelessness, medication misuse, and significant family burden. Similarly, shifting acute care to the home may expose patients and caregivers to new stresses: elevated risk of medical complications, uneven access to technology, cost-shifting, and the potential neglect of those most vulnerable or socially disadvantaged. Historical patterns show that successful community-based care demands strong infrastructure, equitable resource allocation, and thorough patient selection. This manuscript urges stakeholders to heed these lessons and build robust, multidisciplinary, and family-centered systems to support patients transitioning to home care. With proper planning, the current dehospitalization process can achieve its promise of high-quality, cost-effective care without repeating the pitfalls of past reforms.